THE EFFECTIVENESS OF CONTEXTUAL TEACHING AND LEARNING (CTL) IN EDUCATION: A SYSTEMATIC LITERATURE REVIEW AND META-ANALYSIS - Basuki; Sholeh Hidayat; Cecep Anwar Hadi Firdos Santosa (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2025)
The Contextual Teaching and Learning (CTL) approach emphasizes the interconnectedness between academic knowledge and real-life contexts so that learners can build meaningful understanding through authentic experiences. Although many studies on CTL were conducted in Indonesia, the results are still scattered and have not been comprehensively synthesized. Therefore, this study aims to conduct a Systematic Literature Review and meta-analysis to assess the effectiveness of CTL in improving student learning, motivation, communication, and collaboration outcomes in Indonesia. This study uses the Systematic Literature Review (SLR) approach with reference to the PRISMA 2020 guidelines. Articles published between 2013–2025 were searched from Google Scholar, Garuda, Scopus, and DOAJ databases using the keywords "Contextual Teaching and Learning," "effectiveness," "learning outcomes," "motivation," "communication," and "collaboration." Of the 187 articles identified, 19 met the inclusion criteria. The analysis was carried out descriptively, thematically, and quantitatively with a random-effects meta-analysis model. The results of the meta-analysis showed a large and statistically significant combined effect size (SMD = –0.781; 95% CI [–0.938, –0.625]; p < 0.001) with a moderate–high level of heterogeneity (I² = 71.85%). CTL has been proven to improve learning outcomes, intrinsic motivation, and collaborative abilities of students. In addition, the trend of implementing CTL in digital learning and blended learning is increasing in line with the Technological Pedagogical Content Knowledge (TPACK) framework. CTL has proven to be effective at various levels and fields of study in Indonesia. This approach strengthens the theory of constructivism and Self-Determination Theory, and supports the Freedom of Learning policy in shaping 21st-century skills such as critical thinking, communication, and collaboration. Further research is suggested to conduct a cross-border meta-analysis and examine the digital adaptation of CTL in the context of new learning.